Efektivitas Virtual Laboratory dalam Pembelajaran Praktikum Elektronika Terintegrasi Profetik - Hartini, Tri Isti; Martin; Ermawati, Imas Ratna; Widyanti, Sekar Tyas; Permata, Adinda (Universitas Nurul Huda, 2022)
The purpose of this research is to develop a digital information media product about the Virtual Laboratory practicum in learning electronics for physics students. The research was conducted using the Research and Development (R&D) method with the ADDIE model, the product developed was in the form of online practicum/virtual electronics laboratory. The data source is physics education students at FKIP UHAMKA. Data sources were obtained from informants, documents, activity processes and validators. Data collection techniques using questionnaires and documentation, while the data analysis techniques used the gain score test, quantitative and qualitative descriptive analysis. Model validation was carried out using expert judgment using the Delphi technique. The results of this study are (1) online/virtual laboratory practicum models; (2) development of online practicum / virtual laboratory electronics; (3) The web-based student practicum model is feasible to apply. Validation from experts/experts in material academics, media and practitioners related to models and modules is 79.2 and 88.4 in the very good category. In this study, it can be seen that the character / prophetic values ​​of virtual laboratory users have 4 categories of values, namely shidiq which means honest with an average of 8.80, amanah which means responsibility with an average of 9.08 and tabliq / truth / communicative with an average of 9 .33, fathonah which means intelligent/curiosity, with an average of 9.00. The conclusion is that this electronics practicum is effective through a virtual laboratory and is feasible for prophetic training in student practicum on ohm's law and Kirchoff's law.